Bovine tuberculosis surveillance at cattle abattoirs in Ireland, 2008 - Gompo, Tulsi Ram, author; Olea-Popelka, Francisco, advisor; Rao, Sangeeta, committee member; Henao-Tamayo, Marcela, committee member (Colorado State University. Libraries, 2017)
Bovine tuberculosis (TB) surveillance is an ongoing program among abattoirs (slaughterhouses) in Ireland. It is a key complementary tool in addition to the tuberculin skin test to detect infected herds. A retrospective cross-sectional study was conducted to assess the association between potential risk factors and the risk of detection, and the subsequent risk of confirmation of bovine TB lesions for cattle slaughtered in 2008 in Irish abattoirs. Consequently, the abattoirs were ranked based on their efficiencies of detecting suspected bovine TB lesions and their subsequent confirmation in laboratory. A database containing cattle records was obtained from the Center for Veterinary Epidemiology and Risk Analysis (CVERA) at University College Dublin, Ireland, that includes the results of animal movements, tuberculin test results, number of suspected bovine TB lesions detected during slaughter of animals and number of lesions confirmed as Mycobacterium bovis (M. bovis) in laboratory. The known potential risk factors impacting bovine TB lesions detection in Irish abattoirs were animal and herd level characteristics: age, sex, herd type, length of time a herd free from bovine TB after restriction, animal origin and District Electoral Division (DED) risk class. The data were analyzed to control for these potential risk factors when assessing the probability of detecting suspected bovine TB lesions among abattoirs in Ireland. Descriptive analysis was performed to assess the distribution of cattle slaughtered over the different abattoir. Univariable logistic regression was applied to evaluate an association between the risk factors and detection of bovine TB lesions in the abattoirs. Multivariable logistic regression analysis was performed to calculate the adjusted risk of bovine TB lesion detection and confirmation for each abattoir. During 2008, a total of 1,362,195 attested cattle were slaughtered in total thirty-five abattoirs in Ireland. Overall, 3,437 lesions (0.25%, or 25 per 10,000 slaughtered cattle) were detected, and from these, 2,187 (62.68%) bovine TB lesions were confirmed as caused by M. bovis in the laboratory. The crude detection risks varied from 0 to 56 lesions per 10,000 animals slaughtered. The average crude confirmation risks ranged from 0 to 100%. Ultimately, the abattoirs were ranked (1 being the best and 35 the worst) according to their effectiveness of bovine TB lesions detection and confirmation after adjusting the potential risk factors. There is a considerable variability in efficiencies of Irish abattoirs in detecting and confirming bovine TB lesions. It is thus recommended that Irish abattoirs should be monitored regularly with regards their bovine TB slaughter surveillance effectiveness. Also, the abattoirs with lower than expected effectiveness should be strengthened in order to meet the required standards of the Irish bovine TB slaughter surveillance program.